Star Formation History of Dwarf Galaxies in Cosmological Hydrodynamic Simulations - Kentaro Nagamine (Advances in Astronomy)
We examine the past and current work on the star formation (SF) histories of dwarf galaxies in cosmological hydrodynamic simulations. The results obtained from different numerical methods are still somewhat mixed, but the differences are understandable if we consider the numerical and resolution effects. It remains a challenge to simulate the episodic nature of SF history in dwarf galaxies at late times within the cosmological context of a cold dark matter model. More work is needed to solve the mysteries of SF history of dwarf galaxies employing large-scale hydrodynamic simulations on the next generation of supercomputers.